The dying and the doctors the medical revolution in seventeenth-century England - Mortimer, Ian 1967- (Royal Historical Soc. [u.a.], 2009)
From the 16th century onwards, medical strategies adopted by the seriously ill and dying changed radically. This title identifies massive increases in the consumption of medicines and medical advice by various social groups and in various areas. It examines the role of the towns in providing medical services to rural areas and hinterlands.
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Geschichte 1600-1700; Delivery of Health Care / history; Health Services / history; Physicians / history; Pharmacy / history; Plague / history; Smallpox / history; Geschichte; Gesellschaft; Medizin; Delivery of Health Care -- history -- England; Health Services -- history -- England; History, 17th Century -- England; Medical care -- England -- History -- 17th century; Medicine -- England -- History -- 17th century; Physicians -- history -- England; Plague -- history -- England; Public health -- Social aspects -- England -- History; Smallpox -- history -- England; England; England -- Social conditions -- 17th century